Morphological assessment of river stability: review of the most influential parameters - Haron, Nor Azidawati; Yusuf, Badronnisa; Sulaiman, Mohd Sofiyan; Ab Razak, Mohd Shahrizal; Siti Nurhidayu (Multidisciplinary Digital Publishing Institute, 2022)
River health assessments in the form of morphological approaches are crucial to determining the stability of a river system. Human interference in the natural river landscapes has altered the regime of river flows in the past. The catastrophes arising from the regime alteration are varied: excessive erosion and sedimentation, low carrying capacity, depletion of water yield, and many more. Past researchers have formulated numerous assessments to examine the stability of a river system. Still, arguments are prevalent due to the opinionated nature of the evaluation and a lack of parameters about river equilibrium. This paper reviews the past approaches to assessing channel stability by revisiting the most influential parameters adopted in the assessment process. An Analytical Hierarchy Process (AHP) was employed to find the prioritization of the selected parameters. This study found that a field survey is the most preferred method of river assessment instead of the other techniques such as remote sensing, modeling, and rapid field assessment. The most influential parameters (top 5) that determine the stability of a river system are (1) channel forms, (2) channel dimensions, (3) channel substrates, (4) channel pattern, and (5) bank profile. Those parameterizations are crucial to determining the stability of a river system.